Un viaje al pasado: Pompeya según tres relatos de viaje latinoamericanos (1861–1868) - Buitrago Santana, Laura (Collectanea Philologica, 2025)
Since the mid-19th century, traveling to Europe has become a common practice among Latin American elites. The city of Naples, renowned since the 18th century for the Roman sites of Pompeii and Herculaneum, became a must-visit destination. Travelers such as the Peruvian writer and diplomat Pedro Paz Soldán, Colombian politician Aquileo Parra, and Mexican artist Felipe Gutiérrez visited these ruins and left accounts of their experiences. This article aims to examine these testimonies and demonstrate how the experience – made possible by various factors – enabled these individuals to develop their own discourse on antiquity. Moreover, it allowed them to consolidate a cosmopolitan identity that legitimized their privileged social status and contributed to shaping the national identity narratives of their respective countries.